Understanding the role of contextual cues in supporting the formation of medication-taking habits - Katarzyna Stawarz (Frontiers Media S.A., 2015)
Background: Maintaining high adherence is crucial to ensure that medications are effective (WHO, 2003). However, adherence rates are low (e.g. Haynes et al., 2002; Kardas, 2002; Osterberg & Blaschke, 2005). While some patients make a deliberate decision to alter or discontinue their treatment, others can be non-adherent unintentionally (WHO, 2003). Forgetfulness in particular is the main reason of unintentional non-adherence (Unni & Farris, 2011), and several technologies have been designed to support patients' memory. At present, patients have access to a wide range of commercial adherence technologies, from simple smartphone apps to complex medication management systems. The topic is also popular among academic researchers, with many working on novel approaches to supporting patients' memory (e.g. de Oliveira et al., 2010; Lee & Dey, 2014; Rodríguez et al., 2011). However, existing adherence technologies tend to provide timed alerts ("Please take your pill") and largely neglect people's actual behaviour and the context within which they remember their medications. Contextual cues, e.g. routine events or meaningful objects, play an important role in supporting medication adherence, as they aid both prospective memory and habit formation; as a result, medication-taking becomes a part of a daily routine. Tasks linked to routine events, e.g. taking pills with breakfast, are easier to remember than tasks that need to take place at a specific time, such as taking pills at 7am (Park & Kidder, 1996). Moreover, research conducted with older adults shows that medication management is often guided by the physical environment and temporal rhythms of the day (Palen & Aaløkke, 2006), and that it is possible to improve adherence rates through tailoring remembering strategies and leaving visible cues in routinely visited places (Insel & Cole, 2005). Such contextual cues can also support the process of habit formation: as the behaviour is consistently repeated in the presence of stable cues, with time they start to guide the behaviour and provide triggers to action (Lally & Gardner, 2011). However, adherence technologies tend to disregard contextual cues and the habitual nature of many medication regimens, and instead alert users when it is time to take the pill (Stawarz et al., 2014). Similarly, behaviour change technologies designed specifically to support habit formation also neglect contextual cues and instead focus on behaviour tracking and reminders (Stawarz et al, 2015). By supporting the identification and reinforcement of contextual cues, technology could aid both prospective memory and habit formation: it could help patients remember the new regimen and turn it into a reliable medication habit. Aims: Previous research by Stawarz et al. (2015) suggests that contextual cues support habit formation, but because habits take time to develop, people can still forget; conversely, reminders support remembering, but they can inhibit habit development. However, their study measured the development of an artificial habit (texting the researchers), lasted only for 4 weeks, and did not account for the role of location as a contextual cue. Therefore, the aim of this study was to explore the impact of contextual cues and reminders on the development of automaticity of behaviour (representing habit strength) and frequency of repetition (representing adherence to the regimen) over a longer period and with behaviours participants wanted to turn into habit. The understanding of how these factors influence the process of habit formation would enable us to design more effective adherence technologies that assist patients when they start a new regimen (prospective memory support) as well as over the long term (habit support). Method: 209 participants were recruited on social networks, and among students and university staff. They were 18-58 years old (mean age = 27, SD = 7.6 years); 68% were women, 74% were students. They were asked to repeat a healthy behaviour for 3 months and report via SMS the time they completed it. To ensure that the task was meaningful and participants were working towards a habit they would like to develop, before signing up they were given a choice between two simple tasks: a daily meditation habit (focusing on one's breathing for a minute) or drinking more water (one glass). These tasks were selected for these study because they are simple and do not require any specialised tools or resources, which reduces the effort required to complete them every day. 56% of participants selected meditation and 44% selected drinking water as their task. The study had 4 cue conditions informed by previous research: none, SMS reminder, trigger event, trigger event + location. Dependent variables were automaticity and adherence. Self-Report Behavioural Automaticity Index (SRBAI; Gardner et al., 2012) was used to assess automaticity levels at the end of the study. Three months later participants received a follow-up survey that investigated whether they continued with the task. Results: 115 participants completed the study. The results showed that while contextual cues were better at supporting habit formation than reminders, not all cues were equal. Trigger events or time of day had the most impact on supporting the new behaviour, as both helped participants repeat it even when their routine changed (e.g. during holidays). However, relying on location as a trigger was not effective as this cue was too vulnerable to routine changes. The follow-up survey also revealed that while many participants did not develop a daily habit, many developed a habit, e.g. they started carrying a water bottle, meditating during commute or doing breathing exercises when stressed. In addition, in line with previous research, the results showed that while participants who received reminders forgot less often, they reported low automaticity, which indicated that the habit did not develop. Conclusions: To effectively support adherence and help users remember their medications in the long term, technology needs to provide prospective memory reminders and also facilitate habit formation. One way to achieve that is by using reminders to reinforce the associations between the task and its cue to aid habit development while still supporting prospective memory. Future adherence technologies should remind users about their cues ("Please remember to take your medications with breakfast") instead of simply reminding users to act now ("Time to take your medications").